Success factors of imported wood veneer as a material for value-added wood products manufacturing in Malaysia - Chin, Khoon Ark (2019)
A study was carried out to evaluate the trends and attributes of wood veneer species used for door, flooring, and furniture manufacturing in Malaysia. A questionnaire was distributed to 30 value-added wood products manufacturers, in which there were 10 manufacturers in each category: door, engineered-flooring, and furniture. The study assessed the: (1) important wood veneer species used, both local and imported, (2) the reasons for using wood veneers in the manufacture of value-added wood products, and (3) attributes that determined the choice of wood veneer species used for specific wood products. The common local veneers include Rubberwood, Meranti, Nyatoh, Kembang Semangkok, and Bintangor, while the important imported veneers were White Oak, Red Oak, White Ash, Pine, Beech and Cherry. With increasing use of wood-based panels in the manufacture of these products, the use of wood veneers offers a good strategy to maintain aesthetic appeal, without sacrificing strength but at the same time reducing product cost. The factor analysis showed that aesthetic quality and market determinant factors were more important than the sustainability factor in the use of wood veneers in the manufacture of value-added wood products.